Interpersonal polyvictimization: Addressing the care planning needs of traumatized children and youth. (April 2021) - Stewart, Shannon L.; Lapshina, Natalia; Semovski, Valbona
Abstract: Background: Exposure to maltreatment has a detrimental impact on both physical and mental health. However, research on the relationship between polyvictimization and care planning needs is scarce. Objectives: This study investigated the associations between interpersonal polyvictimization and care planning needs for children and youth, controlling for sex and age differences. Participants and settings: The sample included 18, 701 children and youth ( Mage = 12.33, SDage = 3.53) between 4 and 18 years. Participants were recruited from over 58 mental health agencies, facilities, and schools in Ontario, Canada between November 2012 and February 2020. Methods: Multivariate binary logistic regression was used to investigate polyvictimization, sex and age groups, as predictors on care planning outcomes. Significant interaction effects were further examined using simple effects analyses. Results: Children and youth experiencing polyvictimization, compared to those who did not, were more likely to report attachment difficulties, lack of informal support, interpersonal conflict, substance use and harm to self or others. In addition, the relationship between polyvictimization and attachment and interpersonal conflict care planning was moderated by sex. Conclusions: Findings emphasize the importance of focusing on interpersonal polyvictimization and sex differences when developing treatment plans for a variety of care planning needs. Mental health practitioners could utilize the study findings to guide their clinical practices and ensure effective services are provided to those seeking mental health care.